Terapia EMDR en el trastorno límite de personalidad - Mosquera, Dolores; González, Anabel (Acción Psicológica, 2013)
Resumen Los trastornos de personalidad se han asociado a problemas de apego y trauma temprano, siendo de todos ellos el trastorno límite el que presenta unos porcentajes más elevados. La aplicación de terapias orientadas al trauma como EMDR (Desensibilización y Reprocesamiento por Movimientos Oculares) en estos trastornos ofrece interesantes posibilidades para su abordaje. Abstract Personality disorders have been related with early attachment problems and trauma being. borderline personality disorder the one that presents the higher percentage of these factors. EMDR therapy is a recently developed psychotherapeutic approach, with increasing recognition for the treatment of traumatic experiences that offers interesting possibilities for it´s application in personality disorders.